Unleashing the Potential of Renewable Energy in India - Sargsyan, Gevorg (World Bank, 2012)
India has 150 GW of renewable energy potential, about half in the form of small hydropower, biomass, and wind and half in solar, cogeneration, and waste-to-energy. Developing renewable energy can help India increase its energy security, reduce the adverse impacts on the local environment, lower its carbon intensity, contribute to more balanced regional development, and realize its aspirations for leadership in high-technology industries. This diagnostic note draws on a detailed analysis conducted by a PricewaterhouseCoopers India consulting team in 2008-09 for the World Bank. The data are based on information on about 180 wind, biomass, and small hydropower projects in 20 states, as well as information from and norms of the Ministry of New and Renewable Energy (MNRE) and the Central Electricity Regulatory Commission (CERC). The study is intended to provoke discussions of the feasibility of renewable energy development in India. Why is renewable energy development relevant? How much development is economically feasible? What needs to be done to realize the potential? Each of these topics is addressed in a separate chapter, all of which suggest a few implementable measures that India can consider to tap its economically feasible unharnessed potential.